Computer says: oops. (Economist, 2016)
The article discusses a research paper on the accuracy and reliability of the computer programs used by functional magnetic-resonance imaging (fMRI) researchers in scanning the brain of their volunteers. It references a study by Anders Eklund et al., published in an issue of the "Proceedings of the National Academies of Science". It tackles how fMRI works and the method used in the study.